OsCYCP4s coordinate phosphate starvation signaling with cell cycle progression in rice. Issue 7 (9th December 2019) - Xu, Lei; Wang, Fang; Li, Ruili; Deng, Minjuan; Fu, Meilan; Teng, Huiying; Yi, Keke
Abstract: Phosphate starvation leads to a strong reduction in shoot growth and yield in crops. The reduced shoot growth is caused by extensive gene expression reprogramming triggered by phosphate deficiency, which is not itself a direct consequence of low levels of shoot phosphorus. However, how phosphate starvation inhibits shoot growth in rice is still unclear. In this study, we determined the role of OsCYCP4s in the regulation of shoot growth in response to phosphate starvation in rice. We demonstrate that the expression levels of OsCYCP4s, except OsCYCP4;3, were induced by phosphate starvation. Overexpression of the phosphate starvation induced OsCYCP4s could compete with the other cyclins for the binding with cyclin‐dependent kinases, therefore suppressing growth by reducing cell proliferation. The phosphate starvation induced growth inhibition in the loss‐of‐function mutants cycp4;1, cycp4;2, and cycp4;4 is partially compromised. Furthermore, the expression of some phosphate starvation inducible genes is negatively modulated by these cyclins, which indicates that these OsCYCP4s may also be involved in phosphate starvation signaling. We conclude that phosphate starvation induced OsCYCP4s might coordinate phosphate starvation signaling and cell cycle progression under phosphate starvation stress. Abstract : In this study, we identified a class of phosphate starvation‐induced CYCP4s, which negatively regulate plant growth and Pi starvation signaling in rice. CYCP4s may coordinate phosphate starvation signaling and cell cycle progression under phosphate starvation stress.